Kepemimpinan Kepala RA dalam Kompetensi Profesional Guru di RA Nurul Huda - Hidayatur Rosyidah; Ashari Ashari (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The background of this research is the lack of competency possessed by teachers at RA Nurul Huda Jabon Mojoanyar so that the Head of RA wants to strive for teacher competency skills in carrying out their duties as an educator. In addition to the problem of competence in this institution, it is also difficult to find teachers that fit the needs of this school. The head of the RA can only use the teaching staff as they are, not in accordance with their certificates. This study uses a type of qualitative research with data collection techniques in the form of observation, interviews, and documentation. To get the data source obtained from three sources, namely;1) informants ; 2) events/activities; 3) documentation. While data collection in this study used three techniques; 1) observation; 2) interview; 3) documentation. The results of this study are a description of the leadership of the Head of RA Nurul Huda jabon Mojoanyar Mojokerto which found several things including: the head of RA seeks the competence of each teacher to become a professional teacher, the Head of RA has a democratic leadership style, the head of RA builds exemplary attitudes for staff and his subordinates in the madrasa, and the head of the madrasa reflects a firm leadership style.